2017
DOI: 10.1039/c7py00641a
|View full text |Cite
|
Sign up to set email alerts
|

Amphipathic metal-containing macromolecules with photothermal properties

Abstract: Metal-containing macromolecules with extraordinary properties have attracted a great deal of interest owing to their potential application in the development of functional materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…The construction of MPs is a new strategy for signicantly increase the effectiveness of biomedical materials, in particular, to address current issues of traditional methods of treatment and prophylactics. 48,[114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132] Research on MPs in the biomedical eld is impressive. Materials scientists are designing MPs as innovative solutions to improve the effectiveness of DDSs.…”
Section: Introductionmentioning
confidence: 99%
“…The construction of MPs is a new strategy for signicantly increase the effectiveness of biomedical materials, in particular, to address current issues of traditional methods of treatment and prophylactics. 48,[114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132] Research on MPs in the biomedical eld is impressive. Materials scientists are designing MPs as innovative solutions to improve the effectiveness of DDSs.…”
Section: Introductionmentioning
confidence: 99%
“…The unique structure leads to novel properties. Novel metallacycles derived from the reactivity studies of metallapentalynes exhibited great application prospects in various areas, such as near-infrared dyes [47], photothermal therapy [74][75][76][77], phototherapy [78], and self-healing materials [79], enabling their potential applications in materials science and biomedicine. Future developments of metallabenzynes and metallapentalynes and exploration of their potential applications in catalysis [60], materials science and biomedicine would not only extend our perception of aromaticity in metallacycles, but also further enrich fundamental organometallic chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we have reported that the first 12-carbon osmium carbolongcomplexes 2 and 3 show broad absorptions coveringt he region from UV/Vis to near-infrared( NIR) and exhibit excellent photothermal properties. [14] However,t he strategy to prepared erivatives bearing organic functional groups is stilll imited. [12,13] In addition, they were also chemically linked with methoxypolyethylene glycols to improve their water solubility and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] In addition, they were also chemically linked with methoxypolyethylene glycols to improve their water solubility and biocompatibility. [14] However,t he strategy to prepared erivatives bearing organic functional groups is stilll imited. Herein, we report the preparation of new 12-carbon osmium carbolongc omplexes under different reactionc onditions and improved synthetic methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation